Wanderer of the deepest seas : Migratory behaviour and distribution of the highly pelagic Bulwer’s petrel - Dias, Maria P. (2015)
Small-sized nocturnal Procellariiformes are abundant predators in oceanic areas worldwide and are thought to play an important role in many marine food webs as consumers of superabundant mesopelagic prey. However, the spatial ecology and foraging behaviour of the great majority of these species remain largely unknown. We studied the non-breeding distribution and at-sea activity of a migratory small-sized Procellariiform, the Bulwer’s petrels Bulweria bulwerii, from the Selvagem Island colony (subtropical Northeast Atlantic). We found that soon after breeding Bulwer’s petrels migrate towards deep (mean depth of 4416 m), open oceanic waters of the tropical Atlantic, spending the winter far from shelf and shelf-break areas, on regions avoided by most other avian migrants in the Atlantic. When at sea, Bulwer’s petrels spent more time flying during the night ([90 %, all year round) than any other seabird studied so far. This nighttime activity was not influenced by the lunar cycle, suggesting that this highly specialised nocturnal seabird is probably very well adapted to locating and capturing prey even in very dark conditions. The results from the present study may have important implications for the identification of important bird areas in the marine realm, whose boundaries have been delineated so far mostly on the basis of the distribution and behaviour of better studied medium- to large-sized seabirds.